2014
DOI: 10.1111/anae.12636
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dexmedetomidine on inflammatory mediators after cardiopulmonary bypass

Abstract: SummaryCardiac surgery with cardiopulmonary bypass is associated with the development of a systemic inflammatory response that can often lead to dysfunction of major organs. We hypothesised that the highly selective a 2 -adrenergic agonist, dexmedetomidine, attenuates the systemic inflammatory response. Forty-two patients were randomly assigned to receive dexmedetomidine or saline after aortic cross-clamping). The mean (SD) levels of the nuclear protein plasma high-mobility group box 1 increased significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 42 publications
4
102
2
1
Order By: Relevance
“…7,20 In addition, dexmedetomidine was found to reduce systemic inflammatory responses in various conditions, thereby diminishing major organ injury. [21][22][23][24] In clinical settings, however, evidence in that regard is scarce with inconsistent results. Prospective studies showed that dexmedetomidine affected urine output but not postoperative creatinine clearance 25 or exerted no effect on either parameter in patients undergoing coronary artery bypass graft surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,20 In addition, dexmedetomidine was found to reduce systemic inflammatory responses in various conditions, thereby diminishing major organ injury. [21][22][23][24] In clinical settings, however, evidence in that regard is scarce with inconsistent results. Prospective studies showed that dexmedetomidine affected urine output but not postoperative creatinine clearance 25 or exerted no effect on either parameter in patients undergoing coronary artery bypass graft surgery.…”
Section: Discussionmentioning
confidence: 99%
“…6,21 In this study, dexmedetomidine The composite morbidity end points consisted of permanent stroke, acute kidney injury, prolonged ventilator care (448 h), hemostatic reoperation, and deep sternal wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a selective α 2 -agonist and a sedative with anti-inflammatory, 8,9 analgesic, 10,11 and antiemetic effects, 12 and its use for procedural sedation during endoscopy 13 or ablation for atrial fibrillation has been increasing. 14 It is also used for sedation in the intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…1 Also, dexmedetomidine has been investigated as a possible opioid-reducing technique 2 and might attenuate perioperative inflammatory responses. 3 For sedation in intensive care units, a slow titration to effect, with or without a loading dose, is acceptable, because a fast onset of effect is often not necessary. However, during procedural sedation or in the operating room, a faster onset of effect is often desired.…”
mentioning
confidence: 99%